Determining tension distribution and damage evolution patterns in thread-stitched book blocks under cyclic opening conditions - Paliukh, Oleksandr; Kyrychok, Petro; Oliinyk, Volodymyr; Baranova, Daryna (Eastern-European Journal of Enterprise Technologies, 2026)
This study investigates the process behind the stressed-strained state of the thread stitching of a spine part of book blocks at their multiple opening. Most attention is on the spatial work of the thread structure and patterns of load distribution in the spine zone of the block, predetermined by the lack of generalized models for the spatial organization of thread stitching; known approaches mainly consider adhesive or simplified connections. This study is carried out based on structural-mechanical and finite element modeling of the thread structure of spine binding. The proposed model takes into account the spatial trajectory of the thread, the change in direction and tension of the thread in places of bending, as well as its contact interaction with paper. The geometric, force, and finite element models of thread stitching have been constructed. It was established that the tension distribution along the thread trajectory has an exponentially decreasing character. At the same time, the maximum values of the normalized contact pressure p / p0 = 1.0 are observed in the surface stitches of the spine part. The calculations showed that the working interval of thread tension within the Twork = 35–60 conditional units limits ensures stable operation of the thread structure without noticeable evolution of degradation processes in the paper of the folds. At the same time, exceeding the limit tension level of Tpaper = 72 conditional units is accompanied by the gradual development of local damage in the areas of fold openings. After 1000 load cycles, the damage parameter Dp for polyester threads reached 0.96, for cotton threads – 0.87, and for polyamide threads – 0.78. The results could be used to optimize the formation modes of the spatial structure of a thread-glue blinding of the spine part of book blocks